(untitled) (Research, Society and Development, 2021)
The objective of the study was to understand the physiological changes of the sunflower, in the reproductive phase, when submitted to water and saline stresses. The study was conducted in a protected environment, applying 4 irrigation levels (25, 50, 75 and 100% of crop evapotranspiration) and 2 levels of electrical conductivity of irrigation water (0.6 and 3.0 dS m-1) in cultivar Charrua. The design was a randomized complete block design in a 4 x 2 factorial scheme with 3 replicates. Parameters of gas exchange and fluorescence were evaluated. For the gas exchange the photosynthetic rate (A), transpiratory rate (E), stomatal conductance (Gs), internal CO2 concentration (Ci) and the Ci/Ca, A/Ci, A/Gs and A/E. For the chlorophyll A fluorescence, the effective quantum yield of photosystem II (φ PSII), potential quantum yield of photosystem II (Fv / Fm) and photochemical quenching (qP) and non-photochemical quenching (qNP) were measured. The chlorophyll A fluorescence did not change significantly with the treatments. The Charrua showed adaptability to the effects of the stresses, resulting in a decrease in stomatal opening, increases of Gs, A, instantaneous carboxylation efficiency and water use efficiency when submitted to lower levels of irrigation and electrical conductivity.